Phytoradiotherapy: An Integrative Approach to Cancer Treatment by Combining Radiotherapy With Phytomedicines - Alfonzetti, Tyler; Yasmin-Karim, Sayeda; Ngwa, Wilfred; Avery, Stephen (Frontiers in Oncology, 2021)
Radiotherapy (RT) is an effective, but limited method of cancer treatment. While technological advances and a growing understanding of its biological effects have improved its results dramatically, the use of RT is still limited to certain patient populations and by normal tissue toxicities. The harmful side-effects of treating patients with radiation can offset its therapy benefits, limiting its use in certain cases. Phyto, or plant-based, medicines offer a way to add to radiation treatment, while also protecting patients from its toxic side effects. Phytomedicines such as cannabinoids (CBD) and bitter melon extract have demonstrated therapeutic properties, including the ability to activate apoptotic death in cancer cells, diminish tumor progression, and generally decrease the incidence of several cancer types. In addition, herbal drugs have been shown to be powerful antioxidants with the ability to decrease toxicity of RT without the adverse side effects found in synthetic drugs. Furthermore, a number of phytomedicines have been shown to mitigate hypoxic conditions within the tumor microenvironment, creating a more radiosensitive disease and preventing tumorigenesis. The purpose of this article is to examine the merits and demerits of employing phytomedicines during RT. Results from studies that have tested the effects of combining radiotherapy with supplemental herbal treatment are discussed along with perspectives on where additional research is needed to advance “Phytoradiotherapy”. Overall, experimental evidence points to the fact that phytomedicines have significant potential to enhance RT, with need for cross-disciplinary collaborations to establish optimal dosing combinations with evidence-base for clinical translation.